The truth machine : the blockchain and the future of everything - Casey, Michael, 1967-; Vigna, Paul (St Martin's Press, 2018)
Paul Vigna and Michael J. Casey demystify the Internet's next big thing - the Blockchain - and explain why it can restore personal control over our data, assets, and identities and shift the balance of power to revive society's faith in itself. They reveal the disruption it promises for industries including finance, tech, legal, and shipping. This book reveals the empowerment possible when self-interested middlemen give way to the transparency of the blockchain, while highlighting the job losses, assertion of special interests, and threat to social cohesion that will accompany this shift.